Herniasi Medula Spinalis Onset Lambat Pasca-Trauma Akibat Cedera Tulang Belakang Jatuh Rendah: Sebuah Laporan Kasus - Fitriyani, Fitriyani; Ayu, Zahara; Rizqy, Afifah (Medula, 2024)
Traumatic spinal injuries (TSCI) are often caused by falls. Falls are the main cause of TSCI and high falls are becoming more common. Attention should not only be paid to the high incidence of falls, but also to the low incidence of falls due to the higher rate of neurological injuries and their prevalence in the elderly population. We report the case of a 68-year-old patient who experienced progressive deterioration of his neurological condition 1 month after a traumatic spinal cord injury due to a slip. Investigations revealed post-traumatic spinal cord herniation located at the cervical level. Exploration, decompression and repair were carried out immediately. Late-onset post-traumatic spinal cord herniation is a potentially reversible cause of neurological damage after spinal trauma and should be considered in all cases with late neurological damage after spinal trauma.